Exploring the synergistic activation mechanism of mechanochemical processing in the enhancement of high-alumina coal fly ash utilization - Yang, Chennian (Waste management (New York, N.Y.), 2025)
Copyright © 2025 Elsevier Ltd. All rights reserved.